2001
DOI: 10.1021/ac010701u
|View full text |Cite
|
Sign up to set email alerts
|

Direct Voltammetry and Catalysis with Mycobacterium tuberculosis Catalase−Peroxidase, Peroxidases, and Catalase in Lipid Films

Abstract: Stable films of dimyristoylphosphatidylcholine and M. tuberculosis catalase-peroxidase (KatG), several peroxidases, myoglobin, and catalase showed reversible FeIII/FeII voltammetry on pyrolytic graphite electrodes and catalytic current for hydrogen peroxide and oxygen. Amperometric responses for these films to H2O2 at 0 V are likely to contain significant contributions from catalytic reduction of oxygen produced during the catalytic cycles. Relative apparent turnover rates at pH 6 based on steady-state current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
101
4

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(125 citation statements)
references
References 49 publications
20
101
4
Order By: Relevance
“…DMPC films incorporating GOD and peroxidases have demonstrated good analytical responses to glucose. 130 That provides evidence for the feasibility of dual enzyme-lipid films for biosensor fabrication. Another bi-enzymatic biosensor was also constituted through a GOD-entrapping cellulose triacetate membrane, layered onto a polymeric membrane embedding HRP, which was previously blocked onto a pyrolitic graphite electrode.…”
Section: ·5 Other Proteinsmentioning
confidence: 92%
“…DMPC films incorporating GOD and peroxidases have demonstrated good analytical responses to glucose. 130 That provides evidence for the feasibility of dual enzyme-lipid films for biosensor fabrication. Another bi-enzymatic biosensor was also constituted through a GOD-entrapping cellulose triacetate membrane, layered onto a polymeric membrane embedding HRP, which was previously blocked onto a pyrolitic graphite electrode.…”
Section: ·5 Other Proteinsmentioning
confidence: 92%
“…Fe(II) has a very high affinity for oxygen and the latter process is immediately followed by a fast reaction of Protein-Fe(II) with oxygen. (Nakajima, 1987;Onuoha, 1997;Zhang, 2002).…”
Section: Electroacatalytic Activity In Presence Of Oxygenmentioning
confidence: 99%
“…The catalytic reduction of H 2 O 2 exhibits a behavior similar to the one found with oxygen, which suggests that the reaction mechanisms could be similar. Several plausible explanations have been provided in the literature (Nakajima, 1987;Onuoha, 1997;Zhang, 2002), under the assumption that H 2 O 2 can act as an oxidant or reductant agent. It has been suggested that H 2 O 2 reacts with MbFe(III) to give an oxyferryl radical ( • MbFe(IV)=O) which can react again with H 2 O 2 to produce oxygen and Mb(III).…”
Section: Electrocatalysis Of Hydrogen Peroxidementioning
confidence: 99%
“…P450cam which was immobilized on a glassy carbon electrode modified with sodium montmorillonite exhibited reversible redox behavior (Lei et al 2000). Direct electron transfer was reported for several oxygenases that were immobilized on lipid-modified pyrolytic graphite electrodes (Zhang et al 2002). A Co(III) sepulchrate mediator and Pt electrodes were able to transfer electrons to six different P450 monooxygenases (Estabrook et al 1996a;Estabrook et al 1996b;Estabrook et al 1996c).…”
Section: Direct Chemical Reduction Of the Heme Iron Is Very Inefficiementioning
confidence: 93%